A confluência do currículo na criação de textos audiovisuais: uma proposta de uso dos meios para as (i)mediações - Barbiellini, Daniel Amadei Gonçalves (2013)
This Doctoral Thesis concerns on the need of mediated pedagogical practices suporting a narractive curriculum to be shared by teachers and students. The investigation is divided on two parts: one of those is looking through a theoretical reflection based on the following concepts: mediation, critical thinking, curriculum and territory. Those concepts could be found on works of theorists, respectively: Paulo Freire, Jesús-Martín Barbero, Ivor Goodson and Michel Maffesoli. It includes also, an experimental part that had exposed empirically an increase of critical thinking of students on elementary school by a mediated practice on digital storytelling. By influence of Michel Maffesoli s contributions on Ecosophy studies, this investigation demonstrates the meaning of school s territory as a cognitive place that emerges from interactions between individuals, culture and technology